Application of circulating tumor DNA in prospective clinical oncology trials – standardization of preanalytical conditions. Issue 3 (22nd February 2017) - van Dessel, Lisanne F.; Beije, Nick; Helmijr, Jean C.A.; Vitale, Silvia R.; Kraan, Jaco; Look, Maxime P.; de Wit, Ronald; Sleijfer, Stefan; Jansen, Maurice P.H.M.; Martens, John W.M.; Lolkema, Martijn P.
Abstract : Circulating tumor DNA (ctDNA) has emerged as a potential new biomarker with diagnostic, predictive, and prognostic applications for various solid tumor types. Before beginning large prospective clinical trials to prove the added value of utilizing ctDNA in clinical practice, it is essential to investigate the effects of various preanalytical conditions on the quality of cell‐free DNA (cfDNA) in general and of ctDNA in particular in order to optimize and standardize these conditions. Whole blood samples were collected from patients with metastatic cancer bearing a known somatic variant. The following preanalytical conditions were investigated: (a) different time intervals to plasma isolation (1, 24, and 96 h) and (b) different preservatives in blood collection tubes (EDTA, CellSave, and BCT). The quality of cfDNA/ctDNA was assessed by DNA quantification, digital polymerase chain reaction (dPCR) for somatic variant detection and a β‐actin fragmentation assay for DNA contamination from lysed leukocytes. In 11 (69%) of our 16 patients, we were able to detect the known somatic variant in ctDNA. We observed a time‐dependent increase in cfDNA concentrations in EDTA tubes, which was positively correlated with an increase in wild‐type copy numbers and large DNA fragments (> 420 bp). Using different preservatives did not affect somatic variant detection ability, but did stabilize cfDNA concentrations over time. Variant allele frequency was affected by fluctuations in cfDNA concentration only in EDTA tubes at 96 h. Both CellSave and BCT tubes ensured optimal ctDNA quality in plasma processed within 96 h after blood collection for downstream somatic variant detection by dPCR. Abstract : The effects of preanalytical conditions on the quality of circulating tumor DNA (ctDNA) were investigated using blood samples from patients with metastatic cancer. There was a time‐dependent increase in cell‐free DNA (cfDNA) in EDTA tubes, which decreased detection of somatic variant allele frequencies (VAF). Both CellSave and BCT tubes ensure optimal ctDNA quality for up to 96 h.